New data clarifying the taxonomy of European members of the Lepidocyrtus pallidus–serbicus group (Collembola, Entomobryidae) - Mateos, Eduardo; Winkler, Daniel (Zootaxa, 2018)
The genus Lepidocyrtus is fairly well explored in Hungary and was up to now represented by 18 species. Systematic mesofauna survey of a swamp woodland gave us the opportunity to describe the new species, L. florae sp. nov., characterized by the dark blue color, the dorsal macrochaetae formula A0A2aA2A3S3Pa5/00/0101+2 and the absence of scales on the antennae. Related species L. arrabonicus, L. pallidus, L. pseudosinelloides and L. weidneri were also revised with particular attention to clarify the interpretation of the dorsal chaetotaxy of the head. The observed variability in abdominal chaetotaxy of L. pallidus suggests that the only character differentiating between this species and L. weidneri is the labial chaetotaxy, with chaeta r (in L. pallidus) and chaeta R (in L. weidneri). An identification key to European Lepidocyrtus species with dorsal trunk macrochaetae formula 00/0101+2 is also provided.